2017
DOI: 10.7554/elife.19214
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic regulatory transcription factors regulate growth in rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is a pediatric malignacy of muscle with myogenic regulatory transcription factors MYOD and MYF5 being expressed in this disease. Consensus in the field has been that expression of these factors likely reflects the target cell of transformation rather than being required for continued tumor growth. Here, we used a transgenic zebrafish model to show that Myf5 is sufficient to confer tumor-propagating potential to RMS cells and caused tumors to initiate earlier and have higher penetrance. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 80 publications
(160 reference statements)
5
58
2
Order By: Relevance
“…Recent studies have identified a key role for MyoD in driving RMS growth and initiation Tenente et al 2017). During our analysis, we noticed a significant number of MyoD peaks that were gained only in the presence of Twist2 overexpression (Fig.…”
Section: Twist2 Dynamically Regulates Global Chromatin Organization Dmentioning
confidence: 57%
See 1 more Smart Citation
“…Recent studies have identified a key role for MyoD in driving RMS growth and initiation Tenente et al 2017). During our analysis, we noticed a significant number of MyoD peaks that were gained only in the presence of Twist2 overexpression (Fig.…”
Section: Twist2 Dynamically Regulates Global Chromatin Organization Dmentioning
confidence: 57%
“…Twist2-induced changes in chromatin structure prevent MyoD from accessing its physiologic target genes but also enable MyoD to bind new target genes. Recent studies have suggested that MyoD and Myf5 adopt key roles in regulating RMS growth and initiation (Olguín et al 2011;Tenente et al 2017). Through ChIP-seq of ERMS cell lines, Tenente et al (2017) observed that both factors regulate genes involved in muscle development, growth factor signaling, smooth muscle and endothelial cell biology, and TGF-β signaling.…”
Section: Discussionmentioning
confidence: 99%
“…2B and C). Unlike myoblasts, MYF5 is typically missing from RMS, although when present it appears to be mutually exclusive with MYOD1 (21). Another important divergence from normal myogenesis was high expression of the transcriptional amplifier MYCN (Fig.…”
Section: Fp-rms Tumors and Cell Lines Possess A Myogenic Transcriptiomentioning
confidence: 98%
“…During myoblast differentiation, PROX1 expression increases and it regulates the expression of other myogenic factors and components of the muscle contractile machinery (Kivela et al, 2016). In experimental RMS models, myogenic regulatory factors are expressed in the tumors regardless of their cells of origin (Tenente et al, 2017). Through chromatin acetylation, PAX3 – FOXO1 fusion gene has been shown to generate active super enhancers to drive MYOD1 and MYCN, which can then drive the expression of MYOG (Gryder et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…During myogenesis, the temporal expression of myogenic regulatory factors MYOD1, MYF5, MYF6, and myogenin drive differentiation and a terminal cell-cycle exit (Buckingham & Rigby, 2014). RMS cells express most of these factors, yet they fail to execute terminal differentiation (Tenente et al, 2017). It has also been suggested that RMS can arise from mesenchymal progenitor cells that reside in several non-muscular tissues (Charytonowicz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%